INDEPENDENSI KEWENANGAN KOMISI PEMBERANTASAN KORUPSI PASCA PERUBAHAN UNDANG-UNDANG KOMISI PEMBERANTASAN KORUPSI - Muhammad Habibi (Universitas Lampung, 2020)
After the enactment of Law Number 19 of 2019 concerning the Second Amendment to Corruption Eradication Commission (KPK) Law, the position of the KPK which was originally a non-governmental institution is now included in the branch of governmental power branches (Auxiliary State Organs). All corruption eradication institutions (outside the police and prosecutors) that still survive are only the Corruption Eradication Commission, namely an independent commission which has been given pro justitia authority in carrying out acts of corruption so far not without criticism. In carrying out their duties and functions (before the revision of the Act), experts criticized many of the institutions that were